2021
DOI: 10.1186/s12983-021-00445-6
|View full text |Cite
|
Sign up to set email alerts
|

Love bites: male frogs (Plectrohyla, Hylidae) use teeth scratching to deliver sodefrin precursor-like factors to females during amplexus

Abstract: Background Efficient transfer of chemical signals is important for successful mating in many animal species. Multiple evolutionary lineages of animals evolved direct sex pheromone transmission during traumatic mating—the wounding of the partner with specialized devices—which helps to avoid signal loss to the environment. Although such direct transmission modes of so-called allohormone pheromones are well-documented in invertebrates, they are considered rare in vertebrates. Males of several spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 102 publications
1
21
0
Order By: Relevance
“…This passive broadcast of SPF pheromones contrasts with private transfer of SPF proteins when a male D. ocoee abrades the dorsum to a single female with his premaxillary teeth where pheromones are presumably diffused into the female bloodstream rather than stimulate the olfactory system ( Houck et al, 2007 ). Recently, an extremely similar system was discovered in Plectrohyla frogs where males scratch the female dorsum with their teeth delivering SPF expressed by glands in the upper lip ( Schulte et al, 2021 ). Despite the similarity in delivery system, the SPF pheromones of plethodontid salamanders and Plectrohyla frogs are independently derived from the SPFα and SPFβ families, respectively, that arose by gene duplication in a common ancestor of amphibians.…”
Section: Discussionmentioning
confidence: 99%
“…This passive broadcast of SPF pheromones contrasts with private transfer of SPF proteins when a male D. ocoee abrades the dorsum to a single female with his premaxillary teeth where pheromones are presumably diffused into the female bloodstream rather than stimulate the olfactory system ( Houck et al, 2007 ). Recently, an extremely similar system was discovered in Plectrohyla frogs where males scratch the female dorsum with their teeth delivering SPF expressed by glands in the upper lip ( Schulte et al, 2021 ). Despite the similarity in delivery system, the SPF pheromones of plethodontid salamanders and Plectrohyla frogs are independently derived from the SPFα and SPFβ families, respectively, that arose by gene duplication in a common ancestor of amphibians.…”
Section: Discussionmentioning
confidence: 99%
“…The 2D-TFPs found in the breeding glands of L. vaillanti fall into one clade with all SPF sequences extracted from other anuran breeding glands, which clusters with the beta-SPF clade -one of two salamander SPF clades with known SPF pheromone function (marked with alpha and beta). For further information see Bossuyt et al (2019) and Schulte et al (2021).…”
Section: Figure S1mentioning
confidence: 99%
“…Early studies suggested that in anurans, vocal communication was the primary means of interaction [2,3,15]. However, increasing evidence indicates that chemical communication also plays a significant role in the reproduction and courtship behaviors of frogs and toads [5,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%